2021
DOI: 10.1093/schbul/sbab031
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-Temporal Disconnection Within the Presence Hallucination Network in Psychotic Patients With Passivity Experiences

Abstract: Psychosis, characterized by hallucinations and delusions, is a common feature of psychiatric disease, especially schizophrenia. One prominent theory posits that psychosis is driven by abnormal sensorimotor predictions leading to the misattribution of self-related events. This misattribution has been linked to passivity experiences (PE), such as loss of agency and, more recently, to presence hallucinations (PH), defined as the conscious experience of the presence of an alien agent while no person is actually pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…They tested whether PE experiences were associated with the same FP network map that had been previously identified. Post-hoc connectivity analysis demonstrated that reductions in strength between the right MTG and IFG bilaterally was reduced in patients with passivity experiences [65]. Taken together, impaired multisensory integration may lead to difficulties in determining the source and identity of sensorimotor, proprioceptive, and interoceptive signals, and thus, weakening bodily-self processing.…”
Section: Theoretical Models and Mechanismsmentioning
confidence: 97%
See 2 more Smart Citations
“…They tested whether PE experiences were associated with the same FP network map that had been previously identified. Post-hoc connectivity analysis demonstrated that reductions in strength between the right MTG and IFG bilaterally was reduced in patients with passivity experiences [65]. Taken together, impaired multisensory integration may lead to difficulties in determining the source and identity of sensorimotor, proprioceptive, and interoceptive signals, and thus, weakening bodily-self processing.…”
Section: Theoretical Models and Mechanismsmentioning
confidence: 97%
“…Experimenters also identified in patients that weaker connectivity within this network was associated with greater cognitive decline and more FP experiences during the experimental task [66]. In a further study [65], experimenters acquired fMRI data from individuals diagnosed with psychosis who did or not did report passivity experiences. They tested whether PE experiences were associated with the same FP network map that had been previously identified.…”
Section: Theoretical Models and Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…The feeling of presence has long interested psychologists (James, 1902 ), psychiatrists (Jaspers, 1913 ), and neurologists (Critchley, 1979 ), and has recently also been investigated as a clinical symptom. PH has been reported to co-occur with temporoparietal tumors (Brugger et al, 1996 ), epilepsy (Critchley, 1979 ; Brugger et al, 1996 ), stroke (Blanke et al, 2014 ), or schizophrenia (Llorca et al, 2016 ; Stripeikyte et al, 2021 ). Lately, PH has been classified as a frequent early hallucination in Parkinson's disease (Fénelon et al, 2011 ; Bernasconi et al, 2021 ) and Lewy Body dementia (Nagahama et al, 2010 ).…”
Section: Neurology and Neurosciencementioning
confidence: 99%
“…AVHs are defined as hearing and perceiving voices in the absence of an external auditory stimulus. Based on the technology of functional magnetic resonance imaging (fMRI), recent findings suggested that AVHs might be traced back to abnormally intrinsic functional organizations involving multiple brain regions and networks (Cui et al, 2017 ; Hoffman et al, 2007 ; Kumari et al, 2010 ; Northoff & Qin, 2011 ; Scheinost et al, 2019 ; Silbersweig et al, 1995 ; Simons et al, 2010 ; Stripeikyte et al, 2021 ). Although multiple existing conceptual models of AVHs, such as top‐down and bottom‐up (Hugdahl, 2009 ), corollary discharge (Ford et al, 2007 ), nondominant language intrusion (Sommer et al, 2008 ; van Lutterveld et al, 2014 ), and interhemispheric miscommunication (Curcic‐Blake et al, 2013 ; Gavrilescu et al, 2010 ), were indicated by the previous studies, it is unclear which model is the most relevant for AVHs.…”
Section: Introductionmentioning
confidence: 99%